2000
DOI: 10.1046/j.1468-2982.2000.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and trigeminal event-related potentials in migraine

Abstract: Our data suggest trigeminal hyperexcitability in migraineurs. A general increase of nasal chemosensitivity is not supported because of smaller olfactory ERP amplitudes in migraineurs. Olfactory ERPs discriminate better than trigeminal ERPs between migraineurs and controls, emphasizing the significance of the olfactory system in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…Disruption of habituation has been described in diseased state, like tinnitus [80] where deafferentation of acoustic cortex is believed to be the principal pathogenetic mechanism. On the other hand, receptorial dysfunction in visual [81], olfactory [82] and more recently in auditory [83] and vestibular systems [84, 85] have been described in migraine. Could they play any role in generation of functional cortical abnormalities observed in this disease, through mechanisms like those operating in deafferentation?…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…Disruption of habituation has been described in diseased state, like tinnitus [80] where deafferentation of acoustic cortex is believed to be the principal pathogenetic mechanism. On the other hand, receptorial dysfunction in visual [81], olfactory [82] and more recently in auditory [83] and vestibular systems [84, 85] have been described in migraine. Could they play any role in generation of functional cortical abnormalities observed in this disease, through mechanisms like those operating in deafferentation?…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…The predominant theory is that the activation of this nerve results in release of neuropeptides such as substance P, calcitonin gene‐related peptide, and neurokinin A 7,8 . These peptides cause neurogenic inflammation 9–14 . What activates the terminal branches of the trigeminal nerve, however, remains unknown.…”
Section: Commentsmentioning
confidence: 99%
“…Enhanced EP amplitudes (Grosser et al, 2000), diminished (Weiss et al, 2003) or unaltered amplitudes (De Tommaso et al, 2005) have been reported for migraineurs compared to healthy controls. In adult migraineurs, studies that examined nociceptive evoked potentials (EPs) interictally have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%